Comparative study of proteolytic activity of protease-producing bacteria isolated from thua nao - Katekan Dajanta (2018)
Thua nao is a Thai traditional fermented soya bean product with distinct flavour and aroma. This study was carried out to screen the potential protease-producing bacteria during the fermentation process. Of 171 strains, there were 169 bacterial isolates (98.8%) exhibiting proteolytic activity. Two potential isolates namely TN51 and TN69 showing highest activity as indicated by the widest clear zones (2.73 and 2.65 cm, respectively) were selected for further study. Using five different protein-based media, we found that the medium composition had an influence on the enzyme activity. © 2009 by Maejo University.